Measurable training program to improve physical performance: literature review - Fachrul Ihsan, Muhammad; Purba, Ambrosius; Goenawan, Hanna; Satia Graha, Ali; Womsiwor, Daniel (Universitas Nusantara PGRI Kediri, 2021)
This study aims to determine the appropriate training program and portion in order to improve the physical performance of athletes.This literature review inquiry was obtained from various PubMed and Google Scholar databases by entering keywords, namely: Sports, Yoga, Basic Physical Components, MDA and IL6. This inquiry reviewed 33 articles published in national and international online journals and have been accredited. The results literature review done on prior studies show basic physical components can be optimally improved through exercises based on the FITT formula, namely interval training, fartlek, weight training, circuit training, plyometrix, rope jump and PNF. In addition, showed that aerobic and anaerobic exercises decreased MDA levels. However, the control group experienced a very significant increase in MDA levels. High-intensity exercise was found able to trigger releasing inflammatory mediators such as TNF-ά and IL-6. Furthermore, some literature showed that long-term yoga practice can reduce MDA levels and IL-6 levels as it as it increases antioxidant levels and anti imflamatory levels. This literature review is expected to provide comprehensive explanation of good and measurable training programs for athletes, coaches and sports institutions. Thereby, athletes’ physical performance can be optimally improved and injuries can be avoided so that athletes get sports achievements.